2017
DOI: 10.1007/s10549-017-4341-2
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of mammographic breast density with menopausal status and postmenopausal hormone use in relation to the risk of aggressive breast cancer subtypes

Abstract: Purpose We examined the associations of mammographic breast density with breast cancer risk by tumor aggressiveness and by menopausal status and current postmenopausal hormone therapy. Methods This study included 2596 invasive breast cancer cases and 4059 controls selected from participants of four nested case—control studies within four established cohorts: the Mayo Mammography Health Study, the Nurses’ Health Study, Nurses’ Health Study II, and San Francisco Mammography Registry. Percent breast density (PD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 57 publications
2
9
0
Order By: Relevance
“…Importantly, although percent density is highly correlated with body size and breast fat, associations of migration and acculturation with percent density remained after adjustment for women's childhood body size and midlife BMI. These associations were also unlikely due to breast fat given minimal differences in the amount of mammographically non-dense, primarily fat, tissue in the breast, with mostly inverse associations with breast cancer in prior studies (27,30,31). Reasons for differences in the associations of breast cancer risk factors with dense area and percent density, reported in some studies (32)(33)(34), remain mostly unknown, and along with confirmation of our findings in other ethnic and migrant populations, warrant more research.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Importantly, although percent density is highly correlated with body size and breast fat, associations of migration and acculturation with percent density remained after adjustment for women's childhood body size and midlife BMI. These associations were also unlikely due to breast fat given minimal differences in the amount of mammographically non-dense, primarily fat, tissue in the breast, with mostly inverse associations with breast cancer in prior studies (27,30,31). Reasons for differences in the associations of breast cancer risk factors with dense area and percent density, reported in some studies (32)(33)(34), remain mostly unknown, and along with confirmation of our findings in other ethnic and migrant populations, warrant more research.…”
Section: Discussionsupporting
confidence: 55%
“…We also considered racial/ethnic back-grounds in relation to nativity and migration timing, and did not observe significant MBD differences in U.S.-born women of different racial/ethnic backgrounds, with all three groups having higher MBD as compared with foreign-born Hispanic women. The observed associations were consistent for percent density and dense area, both strong risk factors for breast cancer that respectively represent relative and absolute amount of mammographically dense breast tissue (28)(29)(30). The distribution of breast cancer risk factors differed by race/ethnicity and by migration history, with U.S.-born white women having an overall higher prevalence of most risk factors except for younger age at menarche, lack of and shorter breastfeeding, and large BMI, which were more prevalent in U.S.-born African American women.…”
Section: Discussionmentioning
confidence: 63%
“…Furthermore, Kerlikowske et al found excess breast cancer risk with both estrogen (1.99; 1.61–2.46) and estrogen + progestin (2.09; 1.79–2.43) use [ 8 ], while we detected no association with estrogen, positive and similar associations with CEP in both groups, and differential associations with SEP by MD, that seemed limited to women with dense breasts. Yaghjyan et al found that women with dense breasts (comparing percent density > 50% vs. < 10%) who were current users of HRT, had significantly higher risk of breast cancer (OR: 5.34; 95% CI 3.36–8.49) than previous (2.69; 1.32–5.49) or never (2.57; 1.18–5.60) HRT user [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus it is plausible that some of the increased risk of breast cancer related to HRT use is mediated via increase in MD by HRT use, likely estrogen + progestin use, as suggested by our results. In addition, a recent study suggests that high MD is associated with a more aggressive breast cancer tumors type, especially in women taking estrogen + progesterone HRT regimen [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies investigated whether there is an interaction effect between breast density and the known risk factors on breast cancer. It has been shown that the effect of breast density can be increased or decreased by family history, reproductive factors, behavioral factors, and body mass index (BMI) [ 8 , 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%